Da'wa Model Based on Brand Community Value: Qaryah Thayibah Implementation for Villages Fostered by 'Aisyiyah Ponorogo - Imroatul Istiqomah; Maria Ulfa (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2021)
Islamic da'wa's performance is highly influenced by the techniques and tactics used in conjunction with the preaching object. 'Aisyiyah applies a Qoryah Thayyibah group-based da’wa model that is expected to become the Brand Community Value. Each Regional Leader must enforce this program with a minimum of three supported villages. The purpose of Qoryah Thayyibah, in general, is to establish an advanced and dignified Islamic society. This study aimed to identify the implementation of the Qoryah Thayyibah program and the obstacles faced by 'Aisyiyah Ponorogo. The qualitative literary approach was used in this analysis. Accordingly, the data collection was through documentation (identification of documents), observation, and interviews. The inductive reasoning was also used in the analysis to see how the Qoryah Thayyibah program is implemented, and the conclusion was taken from the general statement to a particular statement. The primary sources were the results of interviews with the management of 'Aisyiyah Ponorogo, interviews with Qoryah Thayyibah PW East Java and PDA Ponorogo, the results of Tanwir relevant to Qoryah Thayyibah and supported by other sources, such as articles, documents or writings on the official PDA website of ‘Aisyiyah Ponorogo. 'Aisyiyah Ponorogo has successfully applied the Qoryah Thayyibah in five of the eight intended fields. They faced obstacles in several fields, including spirituality, education, economics, and health.